Efficacy of Sinopharm Vaccine Among Stem Cell Transplant Recipients During Two Peaks of Delta and Omicron variants of COVID-19 - Ghasemi, Ali; Khodashahi, Rozita; Aliakbarian, Mohsen; Khaleghi, Ebrahim; Razmkhah, Baran; Vahdatinia, Mehrsa; Far, Mahdi S.; Bakhti, Omolbanin (Current Drug Safety, 2023)
Background: Considering the dearth of research on the complications of Sinopharm coronavirus disease 2019 (COVID-19) vaccine in immunocompromised individuals and the lack of available data on COVID-19 vaccination from Iran. Objective: This study aimed to investigate the efficacy of vaccine of Sinopharm COVID-19 vaccine and its complications in bone marrow transplant (BMT) recipients. ; Methods: This was a retrospective cross-sectional study conducted on 250 patients with BMT who were referred to Montaserieh Hospital, Mashhad, Iran. Among them, 53 cases who received at least two doses of Sinopharm COVID-19 vaccine from March to January 2021 were entered in this study. The data were extracted from a student dissertation (Code:4000370). Results: Sinopharm vaccine side effects were reported only in 7.7% of the patients, and shingles was the only serious side effect of the Sinopharm vaccine, which was observed only in one case. The results also revealed that Sinopharm COVID-19 vaccine side effects were not related to age or gender. Infection with the Delta variant of COVID-19 was reported in 7.5% (n=4) and no mortality was reported among them. Vaccine failure was reported in 39.6% of the cases; however, no mortality was reported among patients infected with the Omicron variant of COVID-19. Conclusion: In summary, it seems that Sinopharm COVID-19 vaccine adverse effects were not serious among stem cell transplant recipients. However, it may lead to some severe complications in the population. Vaccine failure against the Delta and Omicron variants of COVID-19 has been reported among more than one-third of BMT patients; however, no mortality was observed among BMT patients infected with the new variants of COVID-19.
Keywords: stem cell